Intravenously Administered, Retinoid Activating Nanoparticles Increase Lifespan and Reduce Neurodegeneration in the SOD1G93A Mouse Model of ALS - Medina, David X.; Chung, Eugene P.; Teague, Collin D.; Bowser, Robert; Sirianni, Rachael W. (Frontiers in Bioengineering and Biotechnology, 2020)
Dysregulation of the retinoic acid (RA) signaling pathway is observed in amyotrophic lateral sclerosis (ALS) and other neurodegenerative disorders. Here, we investigated the therapeutic potential of retinoid activation via the RA receptor β (RARβ) in the SOD1G93A mouse model of ALS. Our approach utilized the RARβ agonist adapalene, which we previously found to be neuroprotective in vitro. Adapalene, like most retinoids, is poorly water soluble, which has thus far prevented effective drug delivery in vivo. To address this challenge, we encapsulated adapalene within nanoparticles (Adap-NPs) composed of poly(lactic acid)-poly(ethylene glycol) (PLA-PEG). Our data demonstrate that intravenous administration of Adap-NPs robustly activates retinoid signaling in the CNS. Chronic administration of Adap-NPs resulted in improved motor performance, prolonged lifespan, and neuroprotection in SOD1G93A mice. This study highlights retinoid signaling as a valuable therapeutic approach and presents a novel nanoparticle platform for the treatment of ALS.